The role of indole-3-acetic acid and characterization of PIN transporters in complex streptophyte alga Chara braunii - Kurtović, Katarina; Vosolsobě, Stanislav; Nedvěd, Daniel; Müller, Karel; Dobrev, Petre Ivanov; Schmidt, Vojtěch; Piszczek, Piotr; Kuhn, Andre; Smoljan, Adrijana; Fisher, Tom J; Weijers, Dolf; Friml, Jiří; et al. (The New phytologist, 2025)
Auxin, indole-3-acetic acid (IAA), is a key phytohormone with diverse morphogenic roles in land plants, but its function and transport mechanisms in algae remain poorly understood. We therefore aimed to explore the role of IAA in a complex, streptophyte algae Chara braunii. Here, we described novel responses of C. braunii to IAA and characterized two homologs of PIN auxin efflux carriers: CbPINa and CbPINc. We determined their localization in C. braunii using epitope-specific antibodies and tested their function in heterologous land plant models. Further, using phosphoproteomic analysis, we identified IAA-induced phosphorylation events. The thallus regeneration assay showed that IAA promotes thallus elongation and side branch development. Immunolocalization of CbPINa and CbPINc confirmed their presence on the plasma membrane of vegetative and generative cells of C. braunii. However, functional assays in tobacco BY-2 cells demonstrated that CbPINa affects auxin transport, whereas CbPINc does not. The IAA is effective in the acceleration of cytoplasmic streaming and the phosphorylation of evolutionary conserved targets such as homolog of RAF-like kinase. These findings suggest that, although canonical PIN-mediated auxin transport mechanisms might not be fully conserved in Chara, IAA is involved in morphogenesis and fast signaling processes.
Keywords: biologický transport; Membrane Transport Proteins; Plant Proteins; membránové transportní proteiny; Nicotiana; Indoleacetic Acids; plant evolution; streptophytes; rostlinné proteiny; Biological Transport; fosforylace; kyseliny indoloctové; auxin transport; Chara; buněčná membrána; tabák; Phosphorylation; indole‐3‐acetic acid; Cell Membrane